ALTERNATIVE LEARNING DURING A PANDEMIC: USE OF THE WEBSITE AS A MATHEMATICS LEARNING MEDIA FOR STUDENT MOTIVATION - Suripah Suripah; Weni Dwi Susanti (IKIP Siliwangi and I-MES, 2022)
In March 2020, direct learning activities were transferred online due to the Covid-19 pandemic. There are many alternative technology-based learning media used for online learning systems. However, the use of this media has not been able to increase students' motivation to learn mathematics. One of the media that can be used as an alternative learning media during this pandemic is a website. The purpose of this study was to find out how to use the website as a learning media in the midst of this pandemic, and to determine student learning motivation. This research is a descriptive study with a quantitative approach, the subjects in this study were 25 students of grade 8 and 9 Junior High School. The results of this study were that many students agreed with the use of websites as alternative learning media during this pandemic and students' high motivation to learn mathematics when using the website with an average percentage of 66,3%. From this research, it can be concluded that the website can be an alternative media for learning mathematics in the midst of this pandemic because the website has various advantages that can also increase student learning motivation.